Separation of Some Anionic Dyes Using Reverse Micelles of CTAB and SDS as Efficient Surfactants Adsorbents from Aqueous Medium - Heba M. El Refay; Nagwa Badawy; Amina Hamada; El Shimaa Hassen (International Journal of Chemical Engineering)
Extractive removal of anionic dyes, namely, Color Index (CI) Reactive Blue 222 and Reactive Yellow 145, using reverse micelles based on liquid-liquid extraction (LLE) was carried out from aqueous solutions using different anionic and cationic surfactants (e.g., sodium dodecyl sulfate (SDS) and cetyltrimethylammonium bromide (CTAB), resp.), which dissolved in ethyl acetate as solvent. The reverse micelle principal acts on the dye encapsulated in the solvent in an aqueous micropool. The experiments were carried out by mixing in a simple mixer a given amount of dyes and surfactants dissolved in a solvent in an aqueous process. Due to gravity, the dye is separated from water after the solvent phase is separated from the aqueous phase, including dye encapsulated in reverse micelles. Under various experimental conditions, extraction efficiency was studied, including solution pH, extraction time, initial dye concentration, extractant concentration, temperature, stripping agent, and solvent reusability. Dyes extracted were stripped quantitatively with NaOH solution. Recovery of the solvent and the reuse of dyes and surfactants after extraction of dye molecules from reverse micelles surfactant core considered are very important from an economic point of view. The optimized conditions were 7 ± 0.2 solution pH, 9 × 10−2 mol/L extractant concentration, 1M NaOH stripping agent concentration, 60 min extraction time, 6 × 10−5 mol/L dye concentration, and 1 : 1 aqueous to organic (A/O) ratio. 87–93% of dyes were extracted at experimental optimum conditions.